Retrieval of Marine Surface Slick Dielectic Properties From Radarsat-2 Data via a Polarimetric Two-Scale Model - Quigley, Cornelius; Brekke, Camilla; Eltoft, Torbjørn (IEEE Transactions on Geoscience and Remote Sensing, 2020)
© 2020 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works. The published version of this article is part of Cornelius Quigley's Ph.D. thesis, which is available in Munin at https://hdl.handle.net/10037/20597 We propose the use of a polarimetric two-scale surface scattering model to retrieve the dielectric parameters of oil slick from the polarimetric synthetic aperture radar. The ocean surface is modeled as an ensemble of randomly orientated, slightly roughened, tilted facets, for which the small perturbation model is assumed to be valid under the condition of no tilt. The orientation of the random facets causes a variation in the in-plane and out-of-plane tilt angles. As the original model utilizes both the co-polarization and cross-polarization channels to determine both the dielectric and roughness characteristics simultaneously from a series of look-up tables, the model is adapted from its original form in order to estimate the roughness characteristics of the scattering surface first, before the dielectric properties are inferred. The performance of the altered scattering model is then evaluated by applying it to multiple sets of quad-polarimetric data containing verified oil slicks, acquired from oil-on-water clean-up exercises in the North Sea. Histograms of retrieved values for the modulus of the dielectric constant indicate that the model is able to invert for values similar to the actual value of 2.3, the dielectric constant of pure crude oil at the lower limit, with successively higher values being found up to values of approximately 20 at the edges of the slicks. An error evaluation is also presented and demonstrates that sources of error are related to the alteration of the ...